2007
DOI: 10.1353/csd.2007.0031
|View full text |Cite
|
Sign up to set email alerts
|

Making Connections: A Network Approach to University Disaster Preparedness

Abstract: A network approach to disaster preparedness in university settings is described. Basic network concepts relevant for disaster preparedness and methods for analyzing network data without complex mathematics are presented. A case study of campus mental health and academic units at a midwestern university is presented to illustrate the practical application of network techniques. Results of the network study indicate the existence of few structural ties among organizational units in the university community and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The importance of providing support to ERE became evident as education opportunities mitigate the psychosocial impact of crisis and disasters by providing a sense of routine, stability, structure, and hope for the future, promoting cognitive, emotional and social development improving student's psychological and behavioural well‐being, which may improve educational outcomes (Burde et al., 2017). As such, universities need to be prepared for crisis before they occur (Stein et al., 2007), ensuring that they have the right affordances in place, before a crisis emerge. This includes reliable and adequate ICT platforms, namely, the development of remote evaluation instruments and grading systems.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of providing support to ERE became evident as education opportunities mitigate the psychosocial impact of crisis and disasters by providing a sense of routine, stability, structure, and hope for the future, promoting cognitive, emotional and social development improving student's psychological and behavioural well‐being, which may improve educational outcomes (Burde et al., 2017). As such, universities need to be prepared for crisis before they occur (Stein et al., 2007), ensuring that they have the right affordances in place, before a crisis emerge. This includes reliable and adequate ICT platforms, namely, the development of remote evaluation instruments and grading systems.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, past research into universities' emergency preparedness has identified communication between campus stakeholders as a critical need (Brown et al, 2016). Segmentation of university departments and structures can inhibit communication between key academic, support, and faith-based student services during an emergency (Stein et al, 2007). In a study of university response to a natural disaster, inconsistent post-disaster communication resulted in student confusion about educational continuity (Watson et al, 2011).…”
mentioning
confidence: 99%
“…However, despite having several obstacles, the lecturers at NIPA School of Administration consider that online teaching activities have become a habit that provides convenience and benefits, particularly during the pandemic. Preparation for the use of technology in learning activities carried out by permanent lecturers at NIPA School of Administration forms a process of adaptation and resilience to the use of technology to a large extent to minimize interruption ( Latchem, 2014 ; Stein et al, 2007 ). With good ICT anxiety conditions, permanent lecturers at NIPA School of Administration tend to explore other technologies to balance and even increase distance learning activities ( Balta-Ozkan et al, 2013 ; Venkatesh et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%